Fundamental of Entrepreneurship ENT300 : Flying Apron Cupcake Shop / Nurfatin Zulaika Mohd Nizam - Mohd Nizam, Nurfatin Zulaika (2020)
The Flying Apron Cupcake Shop is a new company in Malaysia. The name of this company is inspired by the owner who loves to bake. “Flying Apron” itself refer to the activities that happen in the kitchen while “Cupcake Shop” refer to the main dish that our company sell. A unique name will attract people to pronounce and easy to remember. Our company are providing cupcake as the main product and also cake and drinks as the side product that will give high satisfaction to our customer